Infinite Variety - Schmidgen, Wolfram (University of Pennsylvania Press, 2021)
Infinite Variety offers a brilliantly learned analysis of a seventeenth-century aesthetic framed not by the rise of secularism, but by its opposite, and embraced by English writers including Thomas Hobbes, Richard Blackmore, John Locke, Jonathan Swift, and Daniel Defoe.
Description based on publisher supplied metadata and other sources
Keywords: Electronic books